2022
DOI: 10.1128/spectrum.02866-22
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Capsule Biosynthesis and Signaling Networks in Cryptococcus neoformans

Abstract: Over the past decades, human fungal pathogens, including C. neoformans , have emerged as a major public threat since the AIDS pandemic, only to gain more traction in connection to COVID-19. Polysaccharide capsules are rare fungal virulence factors that are critical for protecting C. neoformans from phagocytosis by macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…1C). Furthermore, Jang et al found that Yap1 functions upstream of Gat201 during capsule induction (18). The consistent phenotypes observed across components of previously described regulatory pathways provides confidence that these genes are important for CO2 responses.…”
Section: Resultsmentioning
confidence: 63%
“…1C). Furthermore, Jang et al found that Yap1 functions upstream of Gat201 during capsule induction (18). The consistent phenotypes observed across components of previously described regulatory pathways provides confidence that these genes are important for CO2 responses.…”
Section: Resultsmentioning
confidence: 63%
“…Vishniacozyma victoraie stains differ in regard to the presence of absence of a capsule ( de Garcia et al., 2012 ). Examining the lack of a capsule formation by this yeast and the potential for capsule formation under certain conditions warrant future study ( Vitale et al., 2012 ; Jang et al., 2022 ). Lastly, three PBS-exposed mice were reported to have GMS + histiocyte granules.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, both of the benzoquinone carbonyl groups are likely to react with oxime or oxime ether. According to the spectral data of 1 H NMR, 13 C NMR, and HRMS, only one benzoquinone carbonyl group participated in the reaction. To further determine the absolute configuration of the target compound, X-Ray crystallographic analysis was performed (Figure 2B and Table S4 in the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1 H NMR (600 MHz, DMSO-d 6 , TMS): δ 8.18 (d, J = 5.1 Hz, 1H), 7.64 (d, J = 5.1 Hz, 1H), 4.34 (s, 3H), 2.55 (s, 3H). 13 2B and Table S4, respectively.…”
Section: Z)-8-(methoxyimino)-3-methylthieno[3′2':45]benzo[12-d]isoxaz...mentioning
confidence: 99%